2017
DOI: 10.3997/1873-0604.2017062
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial and marine electrical resistivity to identify groundwater pathways in coastal karst aquifers

Abstract: Groundwater movement in karst aquifers is characterised by high‐velocity fissure and conduit flow paths, and in coastal karst aquifers, these act as pathways for saline intrusion and freshwater discharge to the sea. This paper examines groundwater movement in two neighbouring catchments in the west of Ireland that represent canonical coastal karst aquifers dominated by discharges in the intertidal zone and at offshore submarine springs. Terrestrial and surface‐towed marine electrical resistivity tomography, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The use of marine electrical resistivity tomography (ERT) confirmed that these sinkholes are partly hydraulically activated, hence, acting as submarine springs. These sinkholes are generally filled with sediments, yet, there are single examples that indicate the absence of a sediment infill (O'Connell et al 2018). The geology and structure of the telogenetic karst Burren Plateau extends several kilometres off-shore west of the Burren (Gillespie and Sautter 2018), and therefore sinkholes may accompany these structures, yet, to the knowledge of the authors, no detailed studies have yet confirmed this.…”
Section: Study Areamentioning
confidence: 98%
See 2 more Smart Citations
“…The use of marine electrical resistivity tomography (ERT) confirmed that these sinkholes are partly hydraulically activated, hence, acting as submarine springs. These sinkholes are generally filled with sediments, yet, there are single examples that indicate the absence of a sediment infill (O'Connell et al 2018). The geology and structure of the telogenetic karst Burren Plateau extends several kilometres off-shore west of the Burren (Gillespie and Sautter 2018), and therefore sinkholes may accompany these structures, yet, to the knowledge of the authors, no detailed studies have yet confirmed this.…”
Section: Study Areamentioning
confidence: 98%
“…Known locations of SGD are either in conjunction with intertidal springs along the western shore of the Burren Plateau or limited to Bell Harbour and Kinvara Bay (Drew 2003;O'Connell et al 2018) with estimated discharge rates ranging between 0 and 4.3 m 3 /s, and 5-16 m 3 /s respectively (McCormack et al 2014;Schuler et al 2018). On a larger scale, significant areas of sea-surface-temperature anomalies interpreted as SGD were detected on the western side of the Burren Plateau linked to structural geology (Wilson and Rocha 2012).…”
Section: Groundwater Flow and Previous Tracer Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…; O'Connell et al . ), or in combination with other geophysical methods, such as seismic, self‐potential or ground penetrating radar (GPR) (e.g. Delle Rose and Leucci ; Cardarelli et al .…”
Section: Introductionmentioning
confidence: 99%
“…Airborne or ground-based geophysical methods comprise an important, non-invasive tool for mapping the nearsurface distribution of sinkholes (e.g., Krawczyk et al 2012;Malehmir et al 2016;Cueto et al 2018;Pazzi et al 2018;Mohamed et al 2019) and other salt-related structures (e.g., Boubaya, Allek and Hamoud 2011;O'Connell et al 2018;Ikard and Pease 2019) including saline groundwater bodies (Bauer-Gottwein et al 2010). Geophysical surveys can be designed to achieve a specified penetration depth over wide areas at low cost.…”
Section: Introductionmentioning
confidence: 99%